Silver nanoparticles as a sustainable approach to enhance crop health and mitigate seawater-induced salt toxicity in chickpea - Alabdallah, Nadiyah M.; Latif, Salman (Frontiers in Plant Science, 2026)
Silver nanoparticles (AgNPs) have emerged as promising agents for enhancing plant growth and physiological functions in recent years. However, their role in alleviating salt-induced stress in plants is not yet well understood. In this study, we investigated the impact of foliar sprays of AgNPs1 (300 ppm) and AgNPs2 (400 ppm) on the morphological, physiological, and biochemical responses of chickpea (Cicer arietinum L.) seedlings subjected to different levels of salt stress. The chickpea plants were treated with seawater concentrations of 10%, 30%, and 50%, inducing mild, moderate, and severe salt stress. Salt stress significantly inhibited the growth of chickpea, resulting in reductions in both fresh and dry biomass. Additionally, salinity-induced oxidative stress was indicated by elevated malondialdehyde (MDA) levels in chickpea leaves. However, AgNPs, whether applied alone or in combination with salt stress, enhanced several physiological parameters, including chlorophyll content, chlorophyll stability index (CSI), chlorophyll fluorescence (Fv/Fm), and proline levels, while reducing TSS and MDA levels. Moreover, the antioxidant enzyme activity in chickpea leaves improved under salt stress when AgNPs (AgNPs1 and AgNPs2) were applied, suggesting that AgNPs play a key role in mitigating oxidative damage and promoting stress tolerance. Taken together, these results indicate that applying AgNPs can improve the salinity tolerance of chickpea seedlings by enhancing their morphological, physiological, and biochemical responses to salt stress, offering a potential solution for boosting crop yields on salt-affected soils globally.